(untitled) (Revista Argentina de Cirugía, 2021)
Background: cooperative gastric surgery uses simultaneous, intraluminal peroral and intraperitoneal trans-abdominal pathways to localize and treat, in real time, dificult tumors with conventional procedures. The aim is to resect lesions of different etiology with video assited techniques, simultaneous, preserving tissue and functionality, with the benefits of minimally invasive surgery. Objective: the aim of our study was describe our experience in cooperative gastric procedures at the National Cancer Institute in Bogotá, Colombia. Materials and methods: prospective review of a retrospective database. Descriptive analysis of patients in whom cooperative gastric procedures were performed at the National Cancer Institute of Bogotá, Colombia, between October 2012 and November 2016. Results: sixteen laparoscopic endoscopic cooperative procedures were performed; eight of 16 resected tumors were subepithelial; four cases were done for resection of previous positive margins, two epithelial lesions and two for bleeding and palliative control. Fourteen procedures were exogastric, 1 intragastric and 1 transgastric. The operative time was 91 minutes, the average bleeding was 42 cc and negative margins were present in all cases. The mean hospital stay was 4 days. Conclusions: Our study shows that laparoscopic endoscopic cooperative surgery is a safe and feasible technique with acceptable operative times and minimal bleeding in patients with and without comorbidities, preserving the oncological and minimally invasive principles in the treatment of gastric neoplasms.